The effect of disclosure of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on company value (Empirical study on Food and Beverage companies listed on the IDX for the period 2016-2018) - Yufenti Oktafiah; Nurul Akramiah (Politeknik Negeri Madiun, 2021)
High increase in company value is a long-term goal that should be achieved by the company which will be reflected in the market price of its shares because investors' valuation of the company can be observed through the movement of stock prices of companies traded on the stock exchange for companies that have gone public. Company value is the investor's perception of the company, which is often associated with stock prices. Company value is not only measured by the level of profitability. Various studies have concluded that there are many factors that influence the high and low values ​​of a company. One such factor is the disclosure of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG). This study aims to determine specifically the effect of the disclosure of Corporate Social Responsibility and Good Corporate Governance on the value of the company in the food and beverage companies listed on the Stock Exchange in the 2016-2018 period. Taking the research period over the past three years, because in that period CSR disclosures are experiencing a fairly good development, indicated by the increasing number of companies that carry out CSR disclosures in the annual report. This study uses sample data from 11 food and beverage companies listed on the Indonesia Stock Exchange. The results of this study Corporate Social Responsibility (CSR) affect the value of the company. Companies that implement CSR, disclose it in Corporate Social Reporting so that it will get many benefits such as customer loyalty and trust from creditors and investors. Whereas Good Corporate Governance (GCG) influences company value. This can be interpreted that the size of the GCG index received by the company. This means that an increase in GCG will drive an increase in company value.